The Use of Sodium Polyacrylate for Oil-Water Demulsification Process - Sekar Melati Aditya; Samsol Samsol; Havidh Pramadika; Onnie Ridaliani (Penerbitan Universitas Trisakti, 2022)
Oil-water emulsion formation is common in oil fields. The emulsion is a problem which causes an increase in production costs and a decrease in oil quality. Therefore, a demulsifier formulation is needed to overcome these problems. The use of household waste, particularly disposable diapers, is a promising alternative. One of the substances contained in diapers is sodium polyacrylate super absorbent polymer, known as sodium polyacrylate. The substance takes 450 years and 500 years to decompose in the sea and on land. Sodium polyacrylate has inert and hydrophilic properties with the working principle of absorbing and trapping water which is expected to reduce the water content in oil-water emulsions which are mostly produced from old oil wells. In this experiment, diapers were used to separate the emulsion in light crude oil samples which were tested with brine with 20% and 70% salinity at 50oC. Centrifuge was used to speed up the demulsification process within 1 to 3 minutes. It can be concluded that sodium polyacrylate contained in diaper waste can reduce the water content of the emulsion. In addition, the demulsification process by sodium polyacrylae was more stable and higher in brine with a salinity of 70% compared to brine with a salinity of 20%.